Digital Tafsir and the Construction of Religious Authority: A Critical Analysis of Gus Nur’s Quranic Interpretation - Nopriani Hasibuan; Eka Mulyo Yunus; Thohar Ahmad Hsb (Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
The phenomenon of digital tafsir presents a significant challenge to the accuracy and credibility of Quranic interpretation. A controversial case emerged from Gus Nur’s digital sermon, in which he claimed that “scholars can originate from animals,” referring to surah Fāṭir [35]: 28. This claim generated theological confusion and illustrated the potential for interpretive distortion in digital da‘wah. This study investigates the forms and mechanisms of distortion in Gus Nur’s interpretation and critically verifies his claims using authoritative exegetical methods. A qualitative content-analysis approach is employed, drawing on primary data from the GusNur 13 Official YouTube channel and the Quranic text, as well as secondary data from classical and contemporary tafsir literature. The analysis integrates the framework of al-Aṣīl wa al-Dakhīl fī al-Tafsīr (The authentic and the intrusive in Quranic Exegesis) with Pierre Bourdieu’s sociological theory, specifically the concepts of field, habitus, capital, and doxa. The findings reveal that the distortions in Gus Nur’s interpretation function as a symbolic attempt to assert religious authority in the digital sphere, utilizing rhetorical strategies and visual religious symbols to construct legitimacy outside established scholarly structures. The study highlights the urgent need for critical verification of digital religious content and underscores the importance of tafsir literacy grounded in rigorous scientific methodology to preserve the accuracy and integrity of Quranic interpretation